Sistem Membering dan Billing Warnet â€œWinner.NETâ€ - Dias Ayu Budi Utami; Tanthy Aisyah Al Muslih (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Warnet is an alternative alternative place to surf the internet for people who have limited internet access. But over time, cafe presents a more powerful setup to run moderate PC games the market skyrocketed. With the increasing number of foreign and local streamers playing these PC-based games makes many people interested try it. However, considering the cost of assembling a PC is not a nominal value more or less they choose to rent it in the cafe. With thus, today's cafes are more likely to be used for gaming, instead surfing the internet has become commonplace considering the use of smart phones which has been fully utilized. Data base processing in a company is important for manage the flow of data within the company. Besides for speed up data processing, the database is also useful for data security. For manage the input and output data from a database, the system is needed. System useful for facilitating communication between the user and the database. System too useful for printing output so that it becomes easier and more efficient. Therefore, using a database in an internet cafe business has high effectiveness that can help data processing activities in cafe.